The Potential Use of Mushrooms β-Glucans in the Food Industry - Eleftherios, Eleftheriadis; Vassilis, Mavraganis G.; Cleanthes, Israilides (International Journal of Biotechnology for Wellness Industries, 2014)
Many edible mushrooms are considered as “functional” foods having immunomodulatory and anticancer properties. The ability of mushrooms to exert biological effects and modulate immune functions is due to the presence of bioactive compounds with most important the polysaccharides β-glucans. B-glucans are found in bacteria, fungi and plants and act on several immune cell receptors resulting in both innate and adaptive response. The incorporation of β-glucans in various foods and animal feed has the potential of creating novel “functional” food products, with many health benefits to human and animal nutrition.